Assessment of soil salinity and environmental factors in the Kesem irrigation scheme, Afar Region, Ethiopia - Mengistu Jiru; Boja Mekonnen; Henk Ritzema; Fentaw Abegaz (Soil and Water Research)
Soil salinity is a growing problem for agricultural production in irrigated areas of arid and semi-arid regions. The extent of salinity levels has not been fully studied in the Kesem irrigation scheme in Ethiopia's Afar region. The objective of the study was to identify the main issues related to soil salinity and their variations, and to assess the influence of environmental variables on soil salinity using multivariate analysis (MVA). The dominant cations in the soil were found to be soluble Na+, Ca2+ and K+ while SO42-and Cl- were the dominant anions. These ions are responsible for the salinity in the scheme. Groundwater table surveys showed that cultivated fields experienced greater fluctuations in groundwater levels compared to abandoned land due to frequent irrigation. The first two principal components (PCA) explained approximately 60% and 63% of the total variation in salinity for the top and bottom layers, respectively. The difference between the top and bottom layers suggests a management influence. According to redundancy analysis (RDA), the groundwater depth and length of irrigation years were identified as the major environmental factors contributing to 99% and 52% of the variability in salinity, respectively. These findings highlight the importance of considering the rising groundwater levels in future land management decisions.